Oral supplementations with free and dipeptide forms of L-glutamine in endotoxemic mice: effects on muscle glutamine-glutathione axis and heat shock proteins - Cruzat, Vinicius; Pantaleao, L.; Donato Jr, J.; de Bittencourt Jr, P.; Tirapegui, J. (Elsevier Inc, 2014)
Sepsis is a leading cause of death in intensive care units worldwide. Low availability of glutamine contributes to the catabolic state of sepsis. l-Glutamine supplementation has antioxidant properties and modulates the expression of heat shock proteins (HSPs). This study investigated the effects of oral supplementation with l-glutamine plus l-alanine (GLN+ALA), both in the free form and l-alanyl-l-glutamine dipeptide (DIP), on glutamine-glutathione (GSH) axis and HSPs expression in endotoxemic mice. B6.129F2/J mice were subjected to endotoxemia (lipopolysaccharides from Escherichia coli, 5 mg.kg−1, LPS group) and orally supplemented for 48 h with either l-glutamine (1 g.kg−1) plusl-alanine (0.61 g.kg−1) (GLN+ALA-LPS group) or 1.49 g.kg−1 of DIP (DIP-LPS group). Endotoxemia reduced plasma and muscle glutamine concentrations [relative to CTRL group] which were restored in both GLN+ALA-LPS and DIP-LPS groups (P<.05). In supplemented groups were re-established GSH content and intracellular redox status (GSSG/GSH ratio) in circulating erythrocytes and muscle. Thiobarbituric acid reactive substance was 4-fold in LPS treated mice relative to the untreated CTRL group, and plasma TNF-α and IL-1β levels were attenuated by the supplements. Heat shock proteins 27, 70 and 90 (protein and mRNA) were elevated in the LPS group and were returned to basal levels (relative to CTRL group) in both GLN+ALA-LPS and DIP-LPS groups. Supplementations to endotoxemic mice resulted in up-regulation of GSH reductase, GSH peroxidase and glutamate cysteine ligase mRNA expression in muscle. In conclusion, oral supplementations with GLN+ALA or DIP are effective in reversing the conditions of LPS-induced deleterious impact on glutamine-GSH axis in mice under endotoxemia.